(untitled) (Brazilian Journal of Radiation Sciences, 2021)
Non-Aqueous Phase Liquids (NAPLs) compounds are complex mixtures of organic liquids derived from petroleum and/or industrial activity. Contamination of soils and groundwater by NAPLs can generate health and economics problems by compromising water resources; restrict soils use; and cause damage to the public and private patrimony, and the environment. Today there is an increase in areas contaminated by different types of NAPLs, cause of great concern worldwide, due to the difficulty of locating and quantifying contamination, which is a major obstacle that prevents the cleaning of soils and groundwater in affected locations. This work aims to use the concentrations of the Radon gas in the soil as a way to determine areas contaminated by NAPL, using/prove the high affinity of the Radon for NAPLs, which causes the concentration of Radon in the soil to have a deficit in relation to that naturally observed in the studied region. After understanding the affinity of the Radon by the NAPLs, a gas station was located (with the contribution of the city hall of Belo Horizonte – Minas Gerais – Brazil), which went through a diesel oil leak from the storage tank making the area contaminated. Measurements of the Radon concentration were carried out with the AlphaGUARD® Radon monitor. These measurements confirmed the presence of a deficiency in the Radon concentration, which demonstrated its ability to be used as a marker for the presence of NAPL, contributing to future plans remediation and control of pollution, as well as studies of oil wells on-shore.